HUBUNGAN KEBIASAAN MEROKOK DENGAN KEJADIAN HIPERTENSI PADA TAHANAN LAKI-LAKI DI LEMBAGA PEMASYARAKATAN PADANGSIDIMPUAN TAHUN 2018 - Yaturramadhan, Hasni; Ritonga, Nefonafratilova (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Hypertension is one of the most common cardiovascular diseases and is the most common in the community. Hypertension is now a major problem for all of us, not only in Indonesia but in the world because hypertension is one of the entry points or risk factors for diseases such as heart disease, kidney failure, diabetes and stroke. Hypertension is also one of the health problems suffered by most of the assisted residents, where the 2011 health data report received by the Directorate General of Corrections shows that heart disease and blood vessels are among the top 10 diseases in prisons and detention centers. The purpose of this study was to determine the relationship between smoking habits and the incidence of hypertension in male prisoners at the Class IIB Prison in Padangsidimpuan City in 2018. The type of research used was quantitative with an analytical survey method through a cross-sectional approach whose population was all elderly male prisoners in LAPAS Padangsidimpuan City in 2018 amounted to 164 and the number of samples was determined by the Slovin formula, where the results were 64 people. Based on the results of the chi square statistical test, it shows that the p value <alpha value (0.05), meaning that H0 is rejected, it can be concluded that there is a relationship between There is a significant difference between smoking habits and the incidence of hypertension in male prisoners in the Class IIB Penitentiary in Padangsidimpuan City in 2018. It is advised that elderly male prisoners are more aware that smoking is a very important risk factor for exposure to hypertension so that respondents have the intention stop smoking. Keywords: Smoking Habits, Incidence of Hypertension, Male Prisoners, LAPAS Padangsidimpuan City